TINGKAT KEMAMPUAN MOTORIK KASAR SISWA KELAS 5 SD NEGERI 110 PEKANBARU - Alhuda, Muhammad Osama; Vai, Aref; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The main issue in the teaching of Physical Education, Sports, andHealth in elementary schools is the lack of attention to students' motor skills,particularly gross motor skills. Teachers tend to provide only practical material withoutassessing students' motor abilities, causing some students to struggle in the learningprocess. The lack of data on students' motor development results in suboptimal learningprocesses that do not meet individual needs. This study aims to identify and obtaininformation about the gross motor skills of fifth-grade students at SD Negeri 110Pekanbaru. This research is descriptive, as the researcher aims to describe andillustrate the current conditions. The population of this study consists of all fifth-gradestudents at SD Negeri 110 Pekanbaru, totaling 109 students. The sampling techniqueused is purposive sampling, with a research sample consisting of 37 students from classV A. The data analysis technique in this study applies quantitative descriptive statisticalmethods, and the data obtained from the test are adjusted to the norms of the Test ofGross Motor Development (TGMD-2). The results of this study indicate that the grossmotor skills of fifth-grade students at SD Negeri 110 Pekanbaru are generally in theaverage category. Based on the Gross Motor Development Test – 2 (TGMD-2), 32students, or 86.49%, fall within the norm range of 90-110. The final average score ofthe Gross Motor Quotient is 99.27, which also shows that the majority of students havegross motor skills classified as average, indicating that most students possess adequatemotor skills to meet the needs of daily physical activities.Keywords: Students' Gross Motor Skill Level